Efficient removal of arsenic (V) and methyl orange from aqueous solution using hollow magnetic chitosan composite microspheres: Low arsenic concentration, high adsorption capacity, and minimal adsorbent requirement - Zahra Hashemi Jorshahri; Ali Akbari (PLoS ONE, 2025)
In this study, hollow Fe 3 O 4 -SiO 2 -chitosan adsorbent with an optimal chitosan concentration of 2% (w/v) was synthesized to enhance arsenic (V) adsorption performance from low-concentration aqueous solutions. The hollowing process was used to enhance the surface area of the adsorbent and compensate for the surface area reduction of Fe 3 O 4 nanoparticles induced by SiO 2 and chitosan coating layers. Furthermore, the adsorption properties of organic pollutants were evaluated using methyl orange as the adsorbate. The microspheres underwent systematic characterization, and their arsenic (V) and methyl orange adsorption capacities were evaluated under various influencing factors. The results indicated improved surface area (202.174 m 2 /g) compared to non-hollow magnetic adsorbents (110 m 2 /g) reported in previous studies. Complete arsenic (V) removal (100%) was achieved within 60 minutes at a concentration of 0.2 mg/L, using an adsorbent dose of 0.012 g at pH 5. The optimal adsorbent doses for methyl orange (0.1 g/L) and arsenic (V) (0.5 g/L) were notably lower than those reported in previous studies. The electrostatic attraction was likely the dominant mechanism for arsenic (V) adsorption, whereas methyl orange adsorption may involve n-π interactions, hydrogen bonding, and electrostatic forces. The adsorption process followed the pseudo-second-order kinetics model and the Langmuir isotherm, with maximum adsorption capacities of 175.086 mg/g for arsenic (V) at pH 5 and 2399.910 mg/g for methyl orange at pH 3. The adsorbent showed significant potential for removing arsenic (V) and methyl orange, particularly from acidic wastewater. Moreover, the adsorbent maintained significant portion of its initial adsorption capacity for As(V) and methyl orange even in the presence of competing anions such as phosphate, sulfate, chloride, and nitrate. After four adsorption–desorption cycles, it retained over 90% of its adsorption capacity, demonstrating excellent selectivity, stability, and strong potential for the effective removal of both As(V) and methyl orange from aqueous solutions.